Strategies for the conquest of power and the associative sports movement in a changing North African State : The trajectories of personalities between sport and politics from the local to the national level in Algeria - (:unkn) unknown (My University, 2020)
As part of this research, conducted over the past decade, we will take a political look at the sports association movement in Algeria. By taking care not to reduce it to the only political dimension, that is to say to the exploitation made of it by sports leaders and decision-makers, therefore by examining it as a total social phenomenon. Thus, rather than analyzing the Algerian State in its founding dimension, we imagined a new questioning privileging the trajectories of people between the state, the sports association movement and society. Through an investigation of these strategies between sport and politics, it is a question of analyzing the manufacturing of the leaders of a North African state in full mutation, by restoring its dynamics, its functionality and its daily realities around the sports phenomenon.
Keywords: African Research